2020
DOI: 10.3390/ani10071117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Lactating Ewes with Moringa oleifera Leaf Extract on Milk Yield, Milk Composition and Preweaning Performance of Ewe/Lamb Pair

Abstract: The objective this study was to evaluate the effect of different doses of Moringa oleifera leaf extract (MOE) on milk production and milk composition in ewes and on preweaning performance of their lambs. Twenty-four lactating ewes were housed individually with their lambs and assigned to four groups in a completely randomized design. The treatments included a basal diet without MOE (MOE0) or a basal diet supplemented with either 20 mL MOE per ewe per day (MOE20), 40 mL MOE per ewe per day (MOE40) or 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Daily milk yield in the present study was lower compared to recent reports on milk yield from hair sheep ewes. Under tropical conditions, it has been reported that Pelibuey sheep and their crosses have milk daily yields of around 1 to 1.7 kg/d [ 10 , 11 , 12 ]. However, it is important to note that daily milk yields obtained in the present study only correspond to half of the milk produced in a day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily milk yield in the present study was lower compared to recent reports on milk yield from hair sheep ewes. Under tropical conditions, it has been reported that Pelibuey sheep and their crosses have milk daily yields of around 1 to 1.7 kg/d [ 10 , 11 , 12 ]. However, it is important to note that daily milk yields obtained in the present study only correspond to half of the milk produced in a day.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of information regarding dairy production using hair sheep (e.g., Pelibuey) under tropical conditions [ 9 , 10 ]. Recent studies have reported that Pelibuey sheep and their crosses yielded a milk production during their lactation from 1.1 to 1.7 kg/d under tropical conditions [ 10 , 11 , 12 ]. However, detailed data on the milk composition and its potential performance on dairy products from hair sheep is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…The extract was analyzed to determine the presence of bioactive compounds (hydrolyzed tannins, condensed tannins, phenolic compounds, saponins, and flavonoids). Details on extract preparation can be found in a companion paper [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…These changes in milk quality depend on the type of feed. Ruminants are mostly fed on forages; however, forages derived from shrubs contain high amounts of phenolic compounds, tannins, saponins, and flavonoids that are available at relatively low costs, making them a strategy for improving dairy product quality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation